Motives for remitting from Germany to Kosovo - Wiebke Meyer (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2012)
(...) The analyses of the motives for remitting in this research are based on an empirical quantitative dataset collected in 2009/2010. This dataset contains information on 225 Kosovo-Albanian migrants living in Germany and their corresponding rural origin households in Kosovo. This study design is innovative and exceptional for two reasons. First, because usually only one side of the remitting dyad is included in the analysis, i.e. the remitting migrant in the host country or the receiving household at the origin. Second, a new methodology is introduced in the analysis of motives for remitting. It is argued that the common, socio-economic perspective does not suffice to explain the motives for remitting. For this reason, the analysis starts with a common approach for the identification of determinants of remittances using Ordinary Least Squares (OLS). The results are then compared with an analysis based on the Theory of Planned Behaviour (TPB) applied in a Structural Equation Model (SEM). The TPB, borrowed from social psychology, is employed for the first time in this field of research. It is chosen with the purpose of widening the perspective on the motives of remitting through the representation of the inherent cognitive processes that underpin the decision-making process about remitting. The application of the TPB is based on three core constructs: the attitude towards remitting, the perceived norms surrounding remitting, and the perceived control over remitting. It is assumed that these three constructs shape the intention to remit. Additionally, socio-economic determinants, which have shown significance in the common approach, are included. The results of the OLS analysis generally comply with earlier empirical findings. The variables with significant impact on remittances can be split into three groups: (1) the closeness of the relation between the migrant and the origin household; (2) the financial capacity to remit of the migrant; and (3) the need for support by the origin household. It can be confirmed that the closer the relation between the migrant and the relatives at the origin, the better the financial endowment of the migrant; further, the more severe the need for financial support by the origin household is, the higher are the remittances. The results of the TPB approach indicate that the socio-economic determinants contribute to the explanation of the intention to remit only to a small extent. The main impact on the intention to remit stems from the attitude of the migrant towards remitting and the perceived norms on remitting. Consequently, if the migrant has a favourable opinion about remitting and feels that s/he is expected to remit, the intention to remit is stronger. – – (...) Die Analysen zu den Motiven der Rücküberweisungen basieren auf einem empirischen quantitativen Datensatz mit 225 Fällen aus den Jahren 2009/2010. Es wurden sowohl die Geld transferierenden Migranten in Deutschland als auch die dazugehörigen ländlichen Empfängerhaushalte in Kosovo befragt. Dieses Forschungsdesign ist im Hinblick auf seine Zweiseitigkeit außergewöhnlich und innovativ, denn normalerweise wird nur eine Seite, entweder die des Transfersenders oder die der Transferempfänger, direkt befragt. Auch analytisch wird in dieser Arbeit neben dem herkömmlichen Ansatz ein neuer methodischer Weg zur Analyse der Motive eingeschlagen. Es wird in Frage gestellt, ob die geläufige sozio-ökonomische Perspektive ausreicht, um einen detaillierten Einblick in die Motive der Rücküberweisungen zu geben. Ausgehend von einem herkömmlichen Ansatz für die Identifikation der Determinanten der Transfers mit Hilfe von Ordinary Least Squares (OLS) wird anschließend die Perspektive auf die Beweggründe für die Transfers mit Hilfe der Theorie des geplanten Verhaltens erweitert. Diese Perspektiverweiterung hat zum Ziel, die inneren, kognitiven Prozesse des Migranten während der Entscheidungsfindung über Rücküberweisungen abzubilden. Die Ergebnisse der konventionellen Analyse entsprechen weitgehend den Ergebnissen früherer Studien. Die Variablen mit signifikantem Einfluss auf die Transfersummen können dabei in drei Gruppen unterteilt werden: (1) die Enge der Beziehung zwischen Migrant und Empfängerhaushalt, (2) die Ausstattung des Migranten mit finanziellen Mitteln, die Rücküberweisungen ermöglichen, und (3) den Bedarf des Empfängerhaushaltes an finanzieller Unterstützung von Seiten des Migranten. Es kann gezeigt werden, dass die Rücküberweisungen umso höher sind, je enger die Beziehung zwischen Sender und Empfänger, je besser die finanzielle Ausstattung des Migranten und je bedürftiger der Empfängerhaushalt ist. Die Umsetzung der Theorie des geplanten Verhaltens in einem Strukturgleichungsmodell basiert auf drei Kernkonstrukten: die Einstellung gegenüber Rücküberweisungen, die wahrgenommenen Normen, die Rücküberweisungen umgeben, und die wahrgenommene Kontrolle über die Durchführbarkeit der Transfers. Die Theorie geht davon aus, dass diese drei Konstrukte maßgeblich die Handlungsintention bestimmen. Zusätzlich werden die sozio-ökonomischen Determinanten, die im herkömmlichen Ansatz einen signifikanten Einfluss auf die Summe der Transfers gezeigt haben, in die Analyse aufgenommen. Die Ergebnisse dieses innovativen Ansatzes deuten darauf hin, dass die sozio-ökonomischen Determinanten einen vergleichsweise geringen Erklärungsbeitrag zur Intention, Rücküberweisungen zu tätigen, leisten. Der größte Erklärungsbeitrag zur Intention geht von der Einstellung des Migranten gegenüber Rücküberweisungen und den von ihm empfundenen Normen um dieses Verhalten aus. Wenn der Migrant also positiv über Rücküberweisungen denkt und einen Erwartungsdruck ihm gegenüber empfindet, Geld zu schicken, dann ist seine Intention stärker, dieses Verhalten umzusetzen.
urn:nbn:de:gbv:3:2-18784
Keywords: 330